2020
DOI: 10.5216/ree.v22.55122
|View full text |Cite
|
Sign up to set email alerts
|

Facebook® como meio de divulgação científica: aliado ou inimigo?

Abstract: Diferentes estratégias para divulgação de uma nova ferramenta de comunicação e interação em saúde, voltada para pessoas com deficiência, foram aplicadas no Facebook® com o objetivo de identificar quais estratégias de divulgação aplicadas ao Facebook® promoveram mais acessos à rede social D Eficiência e caracterizar seus usuários. Estudo quantitativo, descritivo e longitudinal, com dados extraídos do gerenciador de métricas do Facebook . A divulgação com busca ativa foi superior a passiva, sendo responsável por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
2
1
0
3
Order By: Relevance
“…Regarding the Brazilian regions reached by the boosts on social networks in this study, the Facebook® network had a greater concentration of accesses in the Southeast region (15.18%), a finding also evidenced in the study by Rosa et al, (2020)/ Meanwhile, the Instagram® network boost showed wider distribution among regions such as the Southeast (24.00%) and Northeast (3.68%). Public strategies have been implemented to improve the expansion of internet access, mainly in the northern states of the country.…”
Section: Demographic and Geographic Datasupporting
confidence: 79%
See 1 more Smart Citation
“…Regarding the Brazilian regions reached by the boosts on social networks in this study, the Facebook® network had a greater concentration of accesses in the Southeast region (15.18%), a finding also evidenced in the study by Rosa et al, (2020)/ Meanwhile, the Instagram® network boost showed wider distribution among regions such as the Southeast (24.00%) and Northeast (3.68%). Public strategies have been implemented to improve the expansion of internet access, mainly in the northern states of the country.…”
Section: Demographic and Geographic Datasupporting
confidence: 79%
“…This social network is widely used and has great potential to disseminate information and even fulfill the missions and values of health institutions. A study of the dissemination of a virtual social network highlighted how Facebook® has greater potential for disseminating research and information than other networks, based on the searches and browsing history of people who use this network, reaching a greater number of potential research participants, as well as increasing access to the published material (Rosa et al, 2020).…”
Section: Effect Of Social Networkmentioning
confidence: 99%
“…O questionário virtual (APÊNDICE B) foi previamente validado por profissionais de reabilitação em uma pesquisa de iniciação científica desenvolvida pelo grupo Neurorehab (ROSA et al, 2020; Fonte: Neurorehab, 2020.…”
Section: 42-critérios De Exclusão Da Amostraunclassified
“…O questionário de avaliação do D+Informação foi formulado a partir das pesquisas ativas do grupo Neurorehab (ROSA et al, 2020. Para os testes de associação (independência) foram utilizados Teste Exato de Fischer.…”
Section: Procedimentos Para a Coleta De Dadosunclassified
See 1 more Smart Citation